Science and responsibility for the well-being of the global community. Issue 1 (3rd May 2016) - Forge, John
Abstract : Purpose: The purpose of this paper is to address the topic of the social responsibility and the scientist from a philosophical perspective. This is a (relatively) neglected topic, as philosophers have tended to focus on moral responsibility. Nevertheless, it is important, and timely. Design/methodology/approach: Analytical, based on the author's previous work. This is not an empirical study. Findings: That it is essential for scientists to adopt a global outlook with respect to their social responsibilities. This is in (stark) contrast to the conclusion that would be reached for moral responsibility. Research limitations/implications: In addition to offering some concrete proposals (see below), a general approach to the question is offered that will be useful for further work. Practical implications: Were the suggestions for socially responsible science put into practice, then this would entail a re-orientation of some parts of scientific research; for instance, a moratorium on weapons research. Social implications: The long-run social implications of not re-orienting science, for instance not to focus even more effort on climate change, will be negative in the extreme. Originality/value: The social responsibility of science has always been important, but it is even more important today. By focussing on global responsibility, this paper offers a new approach.